2022
DOI: 10.1371/journal.pone.0268563
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular dynamics of the Sigma-1 receptor observed with super-resolution imaging microscopy

Abstract: Sigma-1 receptor (Sig1R) is an endoplasmic reticulum (ER)-related membrane protein, that forms heteromers with other cellular proteins. As the mechanism of action of this chaperone protein remains unclear, the aim of the present study was to detect and analyze the intracellular dynamics of Sig1R in live cells using super-resolution imaging microscopy. For that, the Sig1R-yellow fluorescent protein conjugate (Sig1R-YFP) together with fluorescent markers of cell organelles were transfected into human ovarian ade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 64 publications
(90 reference statements)
1
2
0
Order By: Relevance
“…We also noticed that unlike previous reports (Mavlyutov et al, 2010), the cerebral cortex, hippocampus, thalamus and olfactory bulb area showed strong immunolabelling of S1Rs by this protocol (Figure S4A, a 1 -a 3 and B, b 1 -b 3 ). Although in images with higher magnifications a background staining of tiny puncta could be seen in WT and KO mice (Figure S5A), Ab #61994 immunolabelling clearly demonstrated the ER-like perinuclear ring structures of the S1R staining as reported in previous studies using EYFP-tagged S1Rs in cultured cells (Hayashi & Su, 2007;Kopanchuk et al, 2022) which was further confirmed by co-labelling an ER marker SERCA2 (Figure S5B). In addition, this protocol could immunolabel S1Rs in other organs such as liver (Figure S6A-D) and heart (Figure S6E-H).…”
Section: Establishment Of a Reliable Protocol For S1r Immunohistochem...supporting
confidence: 83%
“…We also noticed that unlike previous reports (Mavlyutov et al, 2010), the cerebral cortex, hippocampus, thalamus and olfactory bulb area showed strong immunolabelling of S1Rs by this protocol (Figure S4A, a 1 -a 3 and B, b 1 -b 3 ). Although in images with higher magnifications a background staining of tiny puncta could be seen in WT and KO mice (Figure S5A), Ab #61994 immunolabelling clearly demonstrated the ER-like perinuclear ring structures of the S1R staining as reported in previous studies using EYFP-tagged S1Rs in cultured cells (Hayashi & Su, 2007;Kopanchuk et al, 2022) which was further confirmed by co-labelling an ER marker SERCA2 (Figure S5B). In addition, this protocol could immunolabel S1Rs in other organs such as liver (Figure S6A-D) and heart (Figure S6E-H).…”
Section: Establishment Of a Reliable Protocol For S1r Immunohistochem...supporting
confidence: 83%
“…First, Sigma1R-dependent influence on the effects of GABA A R PAMs may be mediated by chaperone properties toward cytoplasmic membrane proteins involved in the regulation of anxiety and seizures [44]. Under misfolded proteins' accumulation conditions (ER stress) or ligand activation, Sigma1R is capable of intracellular translocation within lipid domains, including the plasma membrane region [12,38,81,82]. On the other hand, antagonistic action on the chaperone is able to reduce Sigma1R levels in the cell surface membrane and the expression of α and β subunits of GABA A Rs in vivo [83].…”
Section: Discussionmentioning
confidence: 99%
“…Imaging was performed using a microscope setup as described previously. 66 Briefly, wide-field epifluorescence and TIRF imaging were performed using an inverted microscope based on a Till iMIC body (Till Photonics/FEI, Munich, Germany), equipped with a UPLSAPO 20× oil (NA 0.85) and TIRF APON 60× oil (NA 1.49) objectives (Olympus Co., Tokyo, Japan). The samples were alternately excited using a 405 nm (120 mW) PhoxX laser diode (Omicron-Laserage, Rodgau, Germany) for Hoechst 34580 or at 561 nm (106 mW) for compound 16.…”
Section: Acsmentioning
confidence: 99%
“…Cells were imaged after 30 min of incubation (37 °C, atmosphere with 5% CO 2 ). Imaging was performed using a microscope setup as described previously . Briefly, wide-field epifluorescence and TIRF imaging were performed using an inverted microscope based on a Till iMIC body (Till Photonics/FEI, Munich, Germany), equipped with a UPLSAPO 20× oil (NA 0.85) and TIRF APON 60× oil (NA 1.49) objectives (Olympus Co., Tokyo, Japan).…”
Section: Experimental Sectionmentioning
confidence: 99%